1993
DOI: 10.1007/bf00711576
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the development of individual differences in the hypothalamic-pituitary-adrenal stress response

Abstract: 1. Several years ago, investigators described the effects of infantile handling on the development of hypothalamic-pituitary-adrenal (HPA) responses to stress in the rat. Rat pups exposed to brief periods of innocuous handling early in life showed reduced HPA responses to a wide variety of stressors, and the effect persists throughout the life of the animal. These effects are robust and provide an excellent model for understanding how early environmental stimuli, which are external to the organism, alter neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 97 publications
2
78
0
5
Order By: Relevance
“…Previous reports and the present results are consistent with the possibility that the cognitive benefits of handling only become apparent in a brain that has experienced some neuronal loss. The duration of handling used was shorter than in most studies; Meaney et al 22 found that handling over the second week of life was somewhat less effective than handling over the entire first 3 weeks. To model behavioral intervention after a biological insult to the premature infant brain, we induced injury on P7 and restricted handling to the post-HI period (P8 to P14), a design that may have reduced the power of handling.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous reports and the present results are consistent with the possibility that the cognitive benefits of handling only become apparent in a brain that has experienced some neuronal loss. The duration of handling used was shorter than in most studies; Meaney et al 22 found that handling over the second week of life was somewhat less effective than handling over the entire first 3 weeks. To model behavioral intervention after a biological insult to the premature infant brain, we induced injury on P7 and restricted handling to the post-HI period (P8 to P14), a design that may have reduced the power of handling.…”
Section: Discussionmentioning
confidence: 90%
“…This is consistent with the suggestion that the effects of early handling afford the animal better feedback regulation of the hypothalamic-pituitary-adrenal response to stress. 22 There are several possible mechanisms by which our behavioral intervention might have improved placenavigation performance. We considered the possibility that early behavioral intervention after acute brain injury in neonatal rats might result in a change in lesion size.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, T has been shown to ameliorate mood in hypogonadal and aged men and in perimenopausal and elderly women. T has also been shown to reduce activation of the hypothalamic-pituitaryadrenal (HPA) axis in rats, providing yet another possible mechanism whereby T reduces indices of anxiety (Meaney et al, 1993;Viau and Meaney, 1996;Viau et al, 2001Viau et al, , 2005Viau, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Meaney et al (1993) showed that rats raised by nurturing mothers have increased levels of central serotonin activity compared with rats raised by less nurturing mothers. The increased serotonin activity leads to increased expression of a central glucocorticoid receptor gene.…”
Section: Introductionmentioning
confidence: 99%